Konsep Perbuatan Melawan Hukum Dengan Model Pertanggungjawaban Mutlak (Strict Liability) Dalam Penyelesaian Sengketa Konsumen - Sodikin, Sodikin (PMIH Untag Semarang, 2023)
Law Number 8 of 1999 concerning Consumer Protection regulates legal efforts to resolve consumer disputes through the courts. The lawsuit for damages is based on an unlawful act. The problem is how the concept of unlawful acts is a strict liability model for demanding compensation. The research method used is normative legal research. The results of this study explain that legal remedies through the concept of unlawful acts with this absolute liability model are by interpreting Article 19 paragraphs (1) and (3) of Law Number 8 of 1999. The concept of an unlawful act with a strict liability model is a plaintiff's obligation to prove the existence of a loss without having to prove a mistake. The recommendation is that the Government and the DPR immediately revise Law Number 8 of 1999 by strictly regulating unlawful acts as a legal norm in the law.